A Novel Frameshift Mutation of SCNN1G Causing Liddle Syndrome with Normokalemia. (12th April 2019) - Fan, Peng; Zhao, Yu-Mo; Zhang, Di; Liao, Ying; Yang, Kun-Qi; Tian, Tao; Lou, Ying; Luo, Fang; Ma, Wen-Jun; Zhang, Hui-Min; Song, Lei; Cai, Jun; et al.
Abstract: BACKGROUND: Liddle syndrome (LS) is an autosomal dominant disorder caused by single-gene mutations of the epithelial sodium channel (ENaC). It is characterized by early-onset hypertension, spontaneous hypokalemia and low plasma renin and aldosterone concentrations. In this study, we reported an LS pedigree with normokalemia resulting from a novel SCNN1G frameshift mutation. METHODS: Peripheral blood samples were collected from the proband and eight family members for DNA extraction. Next-generation sequencing and Sanger sequencing were performed to identify the SCNN1G mutation. Clinical examinations were used to comprehensively evaluate the phenotypes of two patients. RESULTS: Genetic analysis identified a novel SCNN1G frameshift mutation, p.Arg586Valfs*598, in the proband with LS. This heterozygous frameshift mutation generated a premature stop codon and deleted the vital PY motif of ENaC. The same mutation was present in his elder brother with LS, and his mother without any LS symptoms. Biochemical examination showed normokalemia in the three mutation carriers. The mutation identified was not found in any other family members, 100 hypertensives, or 100 healthy controls. CONCLUSIONS: Our study identified a novel SCNN1G frameshift mutation in a Chinese family with LS, expanding the genetic spectrum of SCNN1G . Genetic testing helped us identify LS with a pathogenic mutation when the genotypes and phenotype were not completely consistent because of the hypokalemia. This case emphasizes that once a proband is diagnosed with LS by genetic testing, family genetic sequencing is necessary for early diagnosis and intervention for other family members, to protect against severe cardiovascular complications.